Clinical efficacy of low-dose glucocorticoid therapy for critically ill patients with severe fever with thrombocytopenia syndrome: A retrospective cohort study. (May 2023) - Wang, Gang; Xu, Yan-Li; Zhu, Ying; Yue, Ming; Zhao, Jing; Ge, Hong-Han; Ye, Xiao-Lei; Liu, Yuan-Ni; Gong, Xiao-Yi; Zhang, Li-Gang; Geng, Shu-Ying; Chen, Jia-Hao; et al.
Highlights: Efficacy of glucocorticoid therapy in patients with severe fever with thrombocytopenia syndrome depends on the severity of the disease. Glucocorticoid treatment increased fatality in patients with mild disease. Increased fatality was only observed in patients ≤65 years, male, and early admission. Low-moderate glucocorticoids reduced fatality in critically ill patients. Abstract: Objectives: To determine whether glucocorticoids can improve clinical outcomes of severe fever with thrombocytopenia syndrome (SFTS) patients, and how to identify patients who may benefit from the treatment. Methods: A retrospective study was performed to include patients with confirmed SFTS from designated hospitals. The effect of glucocorticoids in reducing case fatality rate (CFR) and improving clinical recovery was evaluated by multivariate logistic regression models. Results: A total of 2478 eligible patients were analyzed, of whom 331 received glucocorticoids. An integrated parameter (L-index) based on Log10 (lactate dehydrogenase*blood urea nitrogen/lymphocyte count) was constructed to discriminate disease severity. In patients with L-index >3.823 indicating severe SFTS, significantly reduced CFR was observed in patients receiving low-moderate glucocorticoid doses with ≤60 mg daily methylprednisolone or equivalent (odds ratio [OR] 0.46, 95% confidence interval [CI], 0.23-0.88), but not in patients receiving high doses. In patients with L-index ≤3.823 indicating mild SFTS, glucocorticoid treatment was significantly associated with increased CFR (OR 3.34, 95% CI, 1.35-9.51), and mainly attributable to high-dose glucocorticoids (OR 2.83, 95% CI, 1.72-4.96). Disaggregated data analysis revealed a significant effect only in patients ≤65 years old, male, and early admission within 7 days after onset, but not in their counterparts. Conclusion: Glucocorticoids are not recommended for mild patients defined by L-index <3.823; however, patients with severe SFTS may benefit from low-moderate doses of glucocorticoids.